2015
DOI: 10.1007/s00253-015-6601-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bioactive anti-CD20 antibody fragments and induction of ER stress response in Arabidopsis seeds

Abstract: Seed-based expression system is an attractive platform for the production of recombinant proteins in molecular farming. Despite the many advantages of molecular farming, little is known about the effect of the different subcellular accumulation of recombinant proteins on the endoplasmic reticulum (ER) quality control system in host plants. In this study, we analyzed the expression of anti-CD20 antibody fragments in seeds of Arabidopsis thaliana (ecotype Columbia) and corresponding glycosylation mutants, and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Well-characterized in vitro propagation, transformation, and maintenance methods of these plants are the factors behind their selection. The protein was expressed in whole plant tissue [66,68,69], leaves [70][71][72][73][74][75], flower [76], seeds [77][78][79][80][81], hairy root culture [82] or tobacco BY-2 (tobacco cultivar Bright Yellow) cells [8,83,84] (Fig. 4).…”
Section: Transformation Methodologies Target Plants and Expression Omentioning
confidence: 99%
“…Well-characterized in vitro propagation, transformation, and maintenance methods of these plants are the factors behind their selection. The protein was expressed in whole plant tissue [66,68,69], leaves [70][71][72][73][74][75], flower [76], seeds [77][78][79][80][81], hairy root culture [82] or tobacco BY-2 (tobacco cultivar Bright Yellow) cells [8,83,84] (Fig. 4).…”
Section: Transformation Methodologies Target Plants and Expression Omentioning
confidence: 99%
“…qPCR using SYBR green detection (5× HOT FIREPol ® EvaGreen qPCR Mix Plus wo ROX, Solis BioDyne) was carried out in a Rotor-Gene 3000 (Corbett Research) with the running profile: 95°C for 12 min followed by 40 cycles of 95°C for 5 s, 55/59°C ( BIP3 / LSM4 ) for 5 s, 72°C for 20 s. The run was completed by a melting analysis from 65 to 95°C rising by 1°C steps. Forward and reverse primers for BIP3 were taken from Wang et al (2015). Small nuclear ribonucleoprotein family protein LSM4 (AT5G27720) was used as internal control gene, using primers 5′ACCACCAGGTGTTGGACGTG3′ and 5′CATCAACCACGGCCGCGAC3′.…”
Section: Methodsmentioning
confidence: 99%
“…In cereals such as maize and rice that accumulate large amounts of endogenous storage protein in ER-derived protein bodies, in some cases, minor distortions of protein body morphology have been detected by electron microscopy upon the expression of recombinant proteins (Yang et al, 2012; Peters et al, 2013; Wang et al, 2013). Other studies have found that recombinant protein synthesis may correlate with an ER stress response (Wang et al, 2015) or cause specific grain phenotypes, such as an opaque endosperm (Oono et al, 2010; De Wilde et al, 2013). The immunolocalization of a recombinant antibody fragment in A. thaliana seeds revealed the aberrant localization of a proportion of KDEL-tagged antibody in the periplasmic space and in ER-derived compartments delimited by ribosome-associated membranes (Van Droogenbroeck et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of secreted recombinant proteins in plants often causes an imbalance between the amount of unfolded protein entering the secretory pathway and the protein folding machinery of the endoplasmic reticulum (ER), resulting in the induction of ER stress and an unfolded protein response (UPR) in which the cell increases its protein-folding capacity (Arcalis et al 2019;de Wilde et al 2013;Oono et al 2010;Wang et al 2015;Pastor-Cantizano et al 2020). The major UPR sensing system appears to be conserved in all eukaryotes, although different organisms utilize different subsets of ER-resident transmembrane sensors.…”
Section: Stress Resilience and Modified Degradation Pathwaysmentioning
confidence: 99%